2014
DOI: 10.1007/s00063-014-0408-6
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss von ECMO und IABP auf die Koronardurchblutung

Abstract: In antegrade perfusion the simultaneous use of IABP and ECMO is useful. In retrograde perfusion IABP impairs the mean arterial pressure and consequently the perfusion of the coronary arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…Next to this, the authors showed that independent of central or peripheral ECMO cannulation settings, adjunctive IABP improved the myocardial oxygen supply-demand balance. Schroeter and colleagues provided an experimental study investigating the impact of additional IABP during peripheral and central ECMO circulation on mean coronary arterial pressure (left anterior descending artery) [17]. The study protocol was performed repetitively for 2 min in several settings (100% ECMO flow vs. 50% ECMO flow).…”
Section: Haemodynamic Effects Of Simultaneous Iabp Support During Ecm...mentioning
confidence: 99%
See 2 more Smart Citations
“…Next to this, the authors showed that independent of central or peripheral ECMO cannulation settings, adjunctive IABP improved the myocardial oxygen supply-demand balance. Schroeter and colleagues provided an experimental study investigating the impact of additional IABP during peripheral and central ECMO circulation on mean coronary arterial pressure (left anterior descending artery) [17]. The study protocol was performed repetitively for 2 min in several settings (100% ECMO flow vs. 50% ECMO flow).…”
Section: Haemodynamic Effects Of Simultaneous Iabp Support During Ecm...mentioning
confidence: 99%
“…Peripheral ECMO canulation leads to a significant decrease in mean coronary arterial pressure with higher myocardial oxygen demand. Moreover, retrograde ECMO circulation without IABP leads to significantly in-creased pressure in the coronary arteries in to antegrade ECMO circulation [17]. The mentioned experimental setting described short-term changes at the beginning of circulatory support.…”
Section: Haemodynamic Effects Of Simultaneous Iabp Support During Ecm...mentioning
confidence: 99%
See 1 more Smart Citation